Sinergy The Role of Social Welfare Institution Holders through Family Care Unit (FCU) - Pranowo, Pranowo; Hidayatullah, A Nururrochman (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research is to reconstruct sinergy the role of social welfare institution holders through family ce unit (FCU), in Citangkil Subdistrict, Citangkil District, Cilegon Municipality, based on consideration that in that location the experiment on FCU was held with the role of social institutions. This research is qualitative-descriptive, describing the implementation and joint-work among the institutions holding FCU program and the commitment of those institutions to materialise plasma family to pioneer family. Data were gathered through interview, either structured and non-structured, observation, and documentary analysis. Data were analysed through SWOPA technic (sthrengthness, weakness, opportunities, problem and action). The research found that the role of social welfare institutions in FCU program in Citangkil Subdistrict still limited on identification and selection activities of pioneer families. The advoction was yet supported by administrative management, facility, and financial. Coordination and unity among institutions should have been optimized, bacaused its human resources in the management should have more dedication to materialise plasma family to be pioneer family